How and when seeking feedback from coworkers pays off? The mixed role of coworker relationship - Zhang, Wei; Qian, Jing; Yu, Haibo (Frontiers in Psychology, 2022)
Although research in the feedback-seeking behavior literature has primarily focused on the feedback seeking from supervisors, some emerging works have begun to explore the benefits of coworker feedback-seeking behavior. Based on social exchange theory, we investigated how and when seeking feedback from coworkers will benefit the seekers. Using a sample of 327 teachers from China, we find that seeking feedback from coworkers is positively associated with task performance and workplace well-being. Seeking feedback from coworkers is also positively associated with coworker relationship. Moreover, coworker relationship mediates the effects of seeking feedback from coworkers and task performance and workplace well-being, and moderates the strength of the relationship between seeking feedback from coworkers on task performance and workplace well-being. Theoretical and practical implications of our findings are discussed.